Breaking the bag habit: Testing interventions to reduce plastic bag demand in a developing country - Armenak Antinyan; Luca Corazzini (Cardiff University, Cardiff Business School, 2023)
Little is known about the impact of interventions aimed at reducing the demand for singleuse plastic bags. In a natural field experiment conducted in a big supermarket chain in Armenia, we test how a nudge (information on the environmental impact of plastic), a competitive financial bonus scheme, and a free provision of reusable bags affect the demand for disposable bags. Relative to the baseline with no intervention, both the bonus and the nudge considerably reduce the purchase of disposable bags. The bonus scheme and the environmental nudge are equally effective when not combined with free reusable bags. However, the financial bonus scheme combined with a free reusable bag is a more potent catalyst of pro-environmental behavior than the environmental nudge combined with a similar bag. Individuals actively use the tote bags to ditch plastic in the presence of a competitive bonus.
Keywords: C93; D12; D91; H23; 330; pro-environmental behavior; nudge; financial bonus; reusable bag; single-use plastic bag; randomized controlled trial